RESPONSE OF FROM OIL PALM EMPTY FRUITS AND EM-4 COMPOSTING ON TOP SOIL MEDIA TO VEGETATIVE GROWTH OF COCOA ( Theobroma cacao L.) - Fenty Maimunah Simbolon; Noverina Chaniago; Joni Pranata Ginting (PT Inovasi Pratama Internasional, 2020)
This research has been carried out at the UISU Agricultural Experimental Field, which is located at Gedung Johor Jln Karyawisata Medan, with height the place ± 25 masl. This research was started from February to April 2016. This study used a factorial randomized block design (RBD) with two factors. The treatments are: Factors for giving palm oil empty fruit bunch compost with various comparisons, namely : K0 = 0 Control, K1 = Topsoil : OPEB Compost (2 : 1), K2 = Topsoil : OPEB Compost (2 : 2) , K3 = Topsoil : OPEB Compost (2 : 3). EM-4 administration factor namely : M0 = 0 Control , M1 = 5 ml/l water, M2 = 10 ml/l water. Observed parameters is plant height, stem diameter, number of leaves, wet weight and heavy dry plants. Results study show that the application of Oil Palm Empty Fruit Bunches had no significant effect on all observed parameters. Application of EM-4. solution no significant effect on plant height, stem diameter , number of leaves, wet weight and heavy dry plants. Application oil Palm Bunch Empty (OPEB ) compost and EM-4 and the combination of the two treatments had no significant effect on all observed parameters.